Golden holocaust: origins of the cigarette catastrophe and the case for abolition - Proctor, Robert N (University of California Press, 2012)
The cigarette is the deadliest artifact in the history of human civilization. It is also one of the most beguiling, thanks to more than a century of manipulation at the hands of tobacco industry chemists. In Golden Holocaust, Robert N. Proctor draws on reams of formerly-secret industry documents to explore how the cigarette came to be the most widely-used drug on the planet, with six trillion sticks sold per year. He paints a harrowing picture of tobacco manufacturers conspiring to block the recognition of tobacco-cancer hazards, even as they ensnare legions of scientists and politicians in a web of denial. Proctor tells heretofore untold stories of fraud and subterfuge, and he makes the strongest case to date for a simple yet ambitious remedy: a ban on the manufacture and sale of cigarettes.